THE PRINCIPLE OF GUILT AS A BASIS FOR CRIMINAL SANCTIONS JUSTIFICATION REVIEW IN THE CRIMINAL LAW IN SERBIA - Ćorović, Emir A. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The principle of guilt is one of the essential principles of criminal law. However, it is a very complex principle. Its content has been presented in this paper particularly referring to a systematic deviation of it in the criminal legislation of the Republic of Serbia. According to the provisions of the article 2 of the Criminal Code of Serbia the principle of guilt is related to punishments and warning measures, while security and educational measures remained beyond its reach. On the other side, The Criminal Code defining a crime offense in the article 14 demands culpability of perpetrator’s behavior. It involves a conceptual problem: a possibility is given for criminal sanctions of the principle of guilt, article 2 of the Criminal Code not referring to security and educational measures could be applied for people acting without culpability. It is paradoxical to accept criminal-justice reaction in the form of criminal sanctions regarding people without guilt. According to author of this paper, such a normative solution brings into issue the relevant principle, more precisely its basis, generality and guidance, the qualities that every legal principle should maintain. Of course, deviations of legal principle and the principle of guilt are possible but they must be kept to a minimum. Otherwise, systematic legal principle deviations, in this case the principle of guilt, are not to be tolerated. Connecting the principle of guilt with the system of criminal sanctions opens the debate on voluntarism embodied in the freedom of will and guilt and positivism/determinism embodied in perpetrator’s danger and educational neglect within the criminal law. It is over a century discussion in the science of criminal law. The author of the paper concludes criminal-justice reaction in the form of criminal sanction can be justified only of based on the principle of guilt. Otherwise, such a reaction has no place in the criminal law. Key words: guilt, freedom of will, blameworthiness, criminal offense, criminal sanctions.
Keywords: criminal sanctions; criminal offense; blameworthiness; freedom of will; guilt